Sexual practices in youth: analysis of lifetime sexual trajectory and last sexual intercourse - Maria Luiza Heilborn; Cristiane S. Cabral
This article examines the sexual practices of young Brazilians based on data from the GRAVAD Research Project, a household survey targeting males and females from 18 to 24 years of age (n = 4,634) in three Brazilian State capitals: Porto Alegre, Rio de Janeiro, and Salvador. The set of practices experienced over the course of their sexual careers is characterized by traits of social belonging, elements from individual life histories, and prescribed rules of conduct for men and women. The authors compared the young people's range of lifetime practices and those from last sexual relations in order to discuss the spread and incorporation of practices into life histories. The data point to the hegemony of vaginal sex in both the lifetime repertoire of sexual practices and the last sexual encounters, such that vaginal sex provides the prime definition of heterosexuality.